Grupo Escolar de Ibiá, MG (1932 a 1946) : uma expressão estadual - Souza, Sirlene Cristina de (2010)
This is a research in the History of Education in Sub History of educational institutions and aims of the Group School Ibiá. The time line includes the year 1932, year of creation and installation of the first primary school in the city of Ibiá region of Triângulo Mineiro/Alto Paranaiba in Minas Gerais, the year 1946 when the group changed its name to Group School Dom José Gaspar. The general objective of this study refers to the recovery of the history of education of educational institution, linked to the political, economic and socio-cultural national, regional and local levels. The hermeneutic of research involves the questioning of facts relating to the expansion of state primary education in Brazil in the period under review, and their impact on the installation process and organization of the School Ibiá. The investigation was developed from the process of institutionalization of the school groups and educational policy of the State through the following categories of analysis: the role of government in education, the place/space for education and the school routine. The heuristic contains quantitative and qualitative data obtained in the consultation of documentary sources, oral and graphic, of the tests explanatory anchored in the dialectical method. Research was carried out searching the dialogical relations between the general and particular, proving that the links in the national and regional influence and/or have caused much of the movement to the School of Ibiá this period. So that the local aspects were related to the historical context in which they have practices and appropriation of school space and time by different individuals that make up the dynamics of the school. From the data it is concluded that much of what has been tried, experienced and/or practiced in this group reflects the direct influence of the state, represented by national or regional government, but yet it is coated with single actions.